Validation test on thresholds for wheelchair power-assist system activation using population data - M. H., Muhammad Sidik; S. A., Che Ghani; R. A. R., Maarof (Science & Engineering Research Support Society, 2020)
Power-assist wheelchair consist of DC motors to ease the propulsion for upper limb impairment person. Surface electromyography (sEMG) is one of methods to activate it. The purpose of this study was to investigate the threshold for Motor Unit Action Potential (MUAP) to activate the power-assist system. MUAPPEAK for contact and recovery phases for 3 participants were collected to be used in validation test to find the most suitable threshold. The threshold are based on mean and standard deviation (SD) of the population data. Result shows no suitable threshold for participant 1, mean for muscle group BIC & TRI for participant 2 (8.77% TP and 0% FN) and participant 3 is fit to both mean and SD for EXT & FIX. As a result, there is no single threshold that fit to all person. Dynamic thresholds or additional threshold determination methods are required to ameliorate the system